Parenting while living with advanced cancer: A qualitative study. (March 2017) - Park, Eliza M; Check, Devon K; Song, Mi-Kyung; Reeder-Hayes, Katherine E; Hanson, Laura C; Yopp, Justin M; Rosenstein, Donald L; Mayer, Deborah K
Background: Patients with advanced cancer who have dependent children are an important population with a life-limiting illness and high levels of psychological distress. Few studies have addressed the experience of being a parent with advanced cancer and their potential palliative needs. Aim: To describe the experience of living with advanced cancer as a parent, including illness experience, parental concerns, and treatment decision making and to explore whether these experiences differ by their functional status. Design: We conducted a cross-sectional, qualitative study using in-depth, semi-structured interviews. Data were analyzed using thematic content analysis. Setting and participants: A total of 42 participants with metastatic cancer and with at least one child under the age of 18 years were recruited from a comprehensive cancer center. 25 participants were rated as having high functional status (the Eastern Cooperative Oncology Group (ECOG) Performance Status Scale = 0–1) and 17 with low functional status (ECOG=2–4). Results: We identified four themes regarding the experience of being a parent with advanced cancer: (1) parental concerns about the impact of their illness and death on their children, (2) "missing out" and losses of parental role and responsibilities, (3) maintaining parental responsibilities despite life-limiting illness, and (4) parental identity influencing decision making about treatment. Parental functional status influenced not only physical responsibilities but also intensified parenting psychological concerns. Conclusion: Parents with metastatic cancer may have unique palliative care needs as they experience parenting concerns while managing the psychological and physical demands of advanced cancer.